Luxury and Rubble : Civility and Dispossession in the New Saigon - Harms, Erik (Anthropologist) (Book collections on Project MUSE., 2016)
"Luxury and Rubble is the tale of two cities within a city. It is the story of two master-planned, mixed-use residential and commercial developments that are changing the face of Ho Chi Minh City. The two developments that Erik Harms examines are examples of urban development projects known in Vietnam as 'New Urban Zones.' These programs, which were born in the early 1990s, are steadily reorganizing the urban landscape in cities across the country. For many Vietnamese, they are a symbol of the country's emergence into global modernity and post-socialist economic reforms. However, they are also sites of great contestation, sparking land disputes and controversies over how to compensate evicted residents. This is a vivid portrayal of urban reorganization along deeply human terms, which delves into the complex and sometimes contradictory experiences of individuals grappling with the forces of privatization in a socialist country"--Provided by publisher